The philosophy of P.F. Strawson - Sen, Pranab Kumar; Strawson, P. F.; Verma, Roop Rekha (Indian Council of Philosophical Research ; Distributed by Allied Publishers, 1995)
Festschrift honoring P.F. Strawson; includes contributed articles on his contributions in logic and on logic.